Understanding the Association Between Constructive Nonconformity and Innovative Work Behavior: an Employee Perspective - Naval Lawande (Australasian Accounting, Business and Finance Journal, 2023)
Purpose: Organizations have evolved to be entities that focus primarily on efficient systems and procedures. This approach was followed by devising techniques or methodologies for employees to conform to these systems or processes. The employee orientation has often been to conform to the status quo rather than to challenge it. Most of the managers believe that cohesion at workplace can be achieved through alignment of behaviors at the workplace. Contrary to this belief, Henry Mintzberg explains, that innovative organizations need to be flexible, reject bureaucracy and most importantly; avoid emphasis on control mechanisms. Hence, the perennial relationship between nonconformance and innovative work behavior is at question here. Also, the ninth Sustainable Development Goal (SDG 9) is fostering innovation. This paper attempts to understand and decipher this relationship between constructive nonconformity (CNC) and innovative work behavior (IWB). Methodology/Approach: Primary data was collected using standardized questionnaire(s) that have been tested in varied contexts. The research question was framed as ‘Does constructive nonconformity influence innovative work behavior?’ The study is based on a survey data conducted on over 459 knowledge workers from an ITES firm in Pune. Findings: The findings indicate that characteristics depicted by constructive nonconformists tend to showcase innovative work behavior. If a constructive nonconformist is allowed to thrive in any work environment, then the goal of innovative work behavior can definitely be achieved. Practical Implications: The paper could have profound implications on managerial decision making, especially in the ITES (Information Technology Enabled Services) sector. The sample is from a single sector, i.e., ITES in India. Future research would benefit from examining the above relationships in other sectors. Hence, the scope for future research in this area is enormous, both contextually and conceptually.
Keywords: Innovative work behavior; nonconformity; work behavior; conformity; employee innovative behaviour